Pacific Water Security and Drought. Fostering Traditional Knowledge Concerns in the South Pacific amidst a Climate Crisis - Orcherton, Dan F. (Journal of Ecohumanism, 2024)
The Pacific region faces increasing challenges of water security and drought due to a current and irreversible climate crisis. This paper examines the impacts of rising temperatures, changing weather patterns, and extreme weather events on freshwater resources across Pacific Island communities. These challenges are exacerbating water scarcity and threatening the basic needs of these vulnerable populations. Traditional knowledge and community-based adaptation strategies have long played a vital role in mitigating water-related risks. However, the severity of the current climate crisis demands an integrative approach that combines scientific research, policy action, and traditional ecological knowledge. This study explores how the integration of Indigenous practices with modern scientific approaches can enhance resilience to drought and freshwater scarcity. It underscores the importance of traditional knowledge systems in sustainable water management, while also recognizing the need for greater focus on how Pacific communities experience climate impacts and respond through local community-based adaptation. By combining local knowledge with scientific data, it is possible to develop culturally appropriate, adaptive water management strategies. This approach aims to build long-term resilience in the Pacific, ensuring communities' access to clean water and safeguarding their overall well-being.